2008
DOI: 10.1111/j.1556-4029.2008.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Child Abuse: Practical Application of Autopsy, Radiological, and Microscopic Studies*

Abstract: A 17-month-old male infant died at home. The infant's right arm was immobilized because of a humeral fracture 1 month earlier. The circumstances of death appeared unclear to the police investigators and a medicolegal autopsy was carried out. External examination revealed diffuse ecchymoses of varying color. Postmortem imaging was performed prior to autopsy (X-rays, multislice computed tomography [MSCT], and focused brain magnetic resonance imaging [MRI]). These investigations revealed four rib fractures of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Another contributing factor could be the inability to detect antemortem or perimortem fractures using conventional diagnostic procedures. Dedouit et al [24] found that multislice computed tomography (MSCT) was a more effective screening method for evaluating skeletal injuries than conventional X-rays. In a swine model study comparing autopsy, radiological, and tomographic diagnostic procedures, Cattaneo et al [25] reported that traditional radiology detected only 47% of fractures, while CT scans detected 34% and autopsy 65%.…”
Section: Discussionmentioning
confidence: 99%
“…Another contributing factor could be the inability to detect antemortem or perimortem fractures using conventional diagnostic procedures. Dedouit et al [24] found that multislice computed tomography (MSCT) was a more effective screening method for evaluating skeletal injuries than conventional X-rays. In a swine model study comparing autopsy, radiological, and tomographic diagnostic procedures, Cattaneo et al [25] reported that traditional radiology detected only 47% of fractures, while CT scans detected 34% and autopsy 65%.…”
Section: Discussionmentioning
confidence: 99%
“…Postmortem imaging has already been successfully used in cases of suspected child abuse, particularly when brain or rib injuries occur [20,21]. This case is a good illustration of the limitations of MSCT.…”
Section: Discussionmentioning
confidence: 90%
“…88,89 Less than 10% of child abuse cases involve serious intraabdominal injuries. 85,90 Nonetheless, all children with suspected abuse must be screened for abdominal injuries because even the most severe injuries can be difficult to diagnose.…”
Section: Identifying Other Comorbid Injuriesmentioning
confidence: 99%